Gross Motor Development of Children with Congenital Heart Disease Receiving Early Systematic Surveillance and Individualized Intervention: Brief Report. (2nd January 2021) - Fourdain, Solène; Simard, Marie-Noëlle; Dagenais, Lynn; Materassi, Manuela; Doussau, Amélie; Goulet, Justine; Gagnon, Karine; Prud'Homme, Joëlle; Vinay, Marie-Claude; Dehaes, Mathieu; Birca, Ala; Poirier, Nancy C.; et al.
ABSTRACT: Purpose : This retrospective study aims to describe the gross motor development of children aged 4 to 24 months with congenital heart disease (CHD) enrolled in a systematic developmental follow-up program and to describe the frequency of physical therapy sessions they received between 4 and 8 months of age. Methods : Twenty-nine infants with CHD underwent motor evaluations using the AIMS at 4 months, and the Bayley-III at 12 and 24 months. Results : Based on AIMS, 79% of 4-month-old infants had a gross motor delay and required physical therapy. Among these, 56.5% received one to two physical therapy sessions, and 43.5% received three to six sessions. Infants who benefited from regular interventions tended to show a better improvement in motor scores from 12 to 24 months. Conclusion : This study highlights the importance of early motor screening in infants with CHD and suggests a potential benefit of early physical therapy in at-risk children. Abbreviations: CHD: Congenital heart disease; AIMS: Alberta Infant Motor Scales; Bayley-III: Bayley Scales of Infant and Toddler Development, Third edition; Bayley-III/GM: Gross Motor section of the Bayley Scales of Infant and Toddler Development, Third edition